2021
DOI: 10.1080/21655979.2021.1883887
|View full text |Cite
|
Sign up to set email alerts
|

Anemia is associated with increased risk of contrast‑induced acute kidney injury: A Systematic Review and Meta-analysis

Abstract: Previous studies have identified numerous risk factors of contrast-induced acute kidney injury (CI-AKI) in patients undergoing coronary angiography. However, the association between anemia and CI-AKI remains conflicting. Thus, we conducted a meta-analysis to further clarify the relationship between anemia and CI-AKI. PubMed, EMBASE and Web of Science were systematically searched from inception to June 2020 to identify eligible studies. The pooled odds ratios (ORs) with 95% confidence intervals (CIs) were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
(34 reference statements)
0
17
2
1
Order By: Relevance
“…Therefore, erythropoietin deficiency in anemia individuals may lead to further deterioration of renal function. 37 However, the present study did not yield similar results, probably since 68% of the patients in the present study were male, and this significant gender imbalance produced a bias. Simultaneously, Pre-procedure renal function was expected in the NSTE-ACS patients enrolled in our study.…”
contrasting
confidence: 68%
“…Therefore, erythropoietin deficiency in anemia individuals may lead to further deterioration of renal function. 37 However, the present study did not yield similar results, probably since 68% of the patients in the present study were male, and this significant gender imbalance produced a bias. Simultaneously, Pre-procedure renal function was expected in the NSTE-ACS patients enrolled in our study.…”
contrasting
confidence: 68%
“…Anemia Systematic review and meta-analysis Wei et al (191) Hypotension Systematic review and meta-analysis Ong et al (192) Volume Depletion and Hemodynamic Instability Systematic review and meta-analysis Tea et al (193) NSAID, diuretics and other nephrotoxic drugs Systematic review and meta-analysis Zhang et al (194) ACE-I/ARB usage Randomized trial parallel-group, single-center CAPTAIN trial (195) Acute heart failure NYHA III-IV Multicenter retrospective study Tian et al (196) Hypoalbuminemia Systematic review and meta-analysis Liwei et al (197) Peri-procedural hyperglycemia Systematic review and meta-analysis Jakrin et al (198) Patient…”
Section: Patient-related Risk Factors-modifiable Weight Of Evidence E...mentioning
confidence: 99%
“…Anemia has been more frequently considered a factor associated with the severity of comorbid disease or poor disease prognosis. The impact of anemia has been reported for AKI episodes in anemic patients who use contrast media 20 , patients with preoperative and postoperative anemia 37 , 38 , and patients with critical illnesses 39 . In our study, we found that anemia (HGB < 13 g/dL) was a risk factor for AKD stage 1.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline HGB and ALB were also divided into high/low HGB (≥ 13 g/dL/ < 13 g/dL) and ALB (≥ 3.5 g/dL/ < 3.5 g/dL) groups. According to these studies 20 , 21 , the definitions of anemia and hypoalbuminemia were HGB < 13 g/dL and ALB < 3.5 g/dL, respectively. The following comorbidities 1 year before the index date were recorded as confounding factors (CKD, hypertension, diabetes mellitus, hyperlipidemia, acute myocardial infarction, ischemic stroke, peripheral artery disease (PAD), chronic obstructive pulmonary disease (COPD), and chronic liver disease (CLD)).…”
Section: Methodsmentioning
confidence: 99%